1996
DOI: 10.1001/archpsyc.1996.01830040075012
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Diagnosis in Child and Adolescent Suicide

Abstract: A limited range of diagnoses--most commonly a mood disorder alone or in combination with conduct disorder and/or substance abuse--characterizes most suicides among teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
812
9
56

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,110 publications
(938 citation statements)
references
References 21 publications
(6 reference statements)
53
812
9
56
Order By: Relevance
“…The SAHA includes both new scales developed specifically for this project and existing scales. In the past several years, the instrument has been modified substantially by the SAHA Research Evaluation Team [23]. The following scales were used for the present study.…”
Section: J Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAHA includes both new scales developed specifically for this project and existing scales. In the past several years, the instrument has been modified substantially by the SAHA Research Evaluation Team [23]. The following scales were used for the present study.…”
Section: J Instrumentsmentioning
confidence: 99%
“…A study [29] in a schoolbased sample of adolescents has shown significant differences in mental health characteristics between suicidal-only and combined suicidal-violent individuals. With regard to clinical risk factors for suicide, the presence of oppositional defiant and conduct disorder was shown to predict suicide attempts in detained males [23]. In reverse, the absence of these two disorders was related to a higher rate of suicide attempts in incarcerated girls [24].…”
Section: Introductionmentioning
confidence: 99%
“…Lebensjahr [1]. In den USA rechnet man, dass fast 1 /4 aller Todesfälle bei Jugendlichen durch Suizide verursacht werden [2]. Für Europa gilt, dass in den meisten Ländern die Selbstmorde unter Minderjährigen zunehmen [3].…”
Section: Jahrgang / Heft 5-6 · 2006 12 April 2006unclassified
“…Als häufigste Risikofaktoren gelten für den Selbstmord im Kindes-und Jugendalter Depressionen, Substanzabusus, aggressive und impulsive Persönlichkeitsstörungen sowie sexueller oder physischer Missbrauch. Hinzuzufügen sind auch psychosoziale Risikofaktoren wie schulischer Stress, Mobbing, Straffällig-keit, gestörte Eltern-Kind-Kommunikation, sowie psychopathologische Auffälligkeiten der Eltern, allen voran Depression und Substanzmissbrauch [2,[4][5][6][7].…”
Section: Jahrgang / Heft 5-6 · 2006 12 April 2006unclassified
See 1 more Smart Citation